Development of an air assisted fuel atomizer (liquid siphon type) for a continuous combustor - Pipatpong Watanawanyoo (2018)
This research was the study of a fuel injection system in continuous combustor. Air atomizing nozzle is developed to good efficiency injection and used low air pressure (68.95-275.79kPa) to assist the atomizing nozzle. Refined palm oil and automotive diesel oil were the fuels the outlet. The aim of design and develop a continuous combustor is emphasized on simplicity for construction, inexpensive, good stability and reduce import fuel for continuous combustor. Material for combustor chamber is stainless steel in order to avoid oxidation at high combustion temperature. The results showed practical combustion performance using refined palm oil as fuel with ultra-low CO and HC emissions less than 206 ppm and 7 ppm. Another main advantage is a clean combustion, as no sulfur content in the fuel. As a result, the combustor performance testing was evaluated with refined palm oil and LPG. By regulating atomizing air pressure between 68.9995-275.79 kPa (10-40psi, Siphon height 0.45 m) and regulating LPG pressure of 6.8 kPa (1 psi), result showed that 0.0001167-0.00019936 kg/s of fuel consumption, hot gas produced from combustion was in the range of 308-4980C depending on oxidizing air mass flow regulated between 0.0695-0.1067kg/s. The LPG mass flow was regulated 0.000489 kg/s in order to sustain the combustion stability. © 2009 Science Publications.